Intercultural Communication of Nusantara Module Students at Slamet Riyadi University - Andri Astuti Itasari (Formosa Journal of Applied Sciences, 2023)
This study aims to determine intercultural communication between students of the Nusantara Module Independent Student Exchange (PMM) at Slamet Riyadi University due to cultural differences. This study uses qualitative research using case studies. Data obtained by observation, in-depth interviews, and documentation. The results showed that there was good communication and interaction between PMM students at Slamet Riyadi University. This interaction creates a sense of mutual tolerance and respect for one another in the city of Solo. The main language used is Indonesian, but it is also supported by the languages of each region, which, of course, learn from one another. The differences that exist actually make students more compact and familiar.